Estudio de la incidencia de Brasinoesteroides en el cultivo de Lechuga (Lactuca Sativa L.), en San Vicente de Pusir, Cantón Bolívar, Provincia de Carchi, 2017 - Chapi Camargo, Tatiana Elizabeth (2018)
VII. SUMMARY The present study was carried out with the objective of determining the yield of two varieties of lettuce,with the application of Brassinosteroids, in San Vicente de Pusir, canton Bolívar, province of Carchi; at 1700msnm.The treatments were: the application of three foliar doses of Brassinosteroids, in the varieties of cabbage lettuce: Road Runner and Patagonia, more the witnesses of the lettuce varieties. The Randomized Complete Blocks Design (DBCA) was used with six treatments and three repetitions,with a factorial arrangement of (A x B) + 2.The variables evaluated were subjected to the adeva, when significant differences were obtained, the Tukey test was applied at 5% probability;of the results obtained, high significance of blocks was determinedin the plant height variable at 30 days after transplantdetermining high significance,also in the variable appearance of cabbage in three treatments resulted in statistically equal,and for the variable days to flowering it was obtained as a result that statistically they are equal;the highest yield was obtained with the Road Runner variety,without the use of brassinosteroids with a total of 62504 kg / haand the best economic performance was obtained with the Road Runner varietyaccording to the benefit / cost ratio, it turns out that for every dollar invested, 10.89 dollars is recovered.